Assessment of Plant Invasions in Agroecosystems of Kashmir Himalaya for Better Management - Dar, Pervaiz A.; Reshi, Zafar A. (Frontiers in Agronomy, 2022)
Weeds, unwanted plants, are responsible for significant yield and economic loss in agroecosystems and pose a serious threat to the ecology and efficiency of these ecosystems. Despite these losses, not much is known about the weeds associated with crops grown in Kashmir Himalaya. Here, we present a complete inventory of weeds associated with rabi crops, such as mustard (Brassica campestris), wheat (Triticum aestivum), flax (Linum usitatissimum), oats (Avena sativa), kharif crop, such as paddy (Oryza sativa), besides apple and other fruit tree orchards. A total of 198 weeds were recorded belonging to 47 families were recorded. Poaceae (27 species) and Asteraceae (23 species) included the highest number of species. Most of these weeds were non-native (136 species) and only 62 species were native. 51 non-native species were invasive. Most of the weeds were herbs (195 species). Annuals and perennials were almost equally represented with 93 and 92 species, respectively. The number of weeds varied across the surveyed crops with the highest number of species (104) recorded in orchards and the lowest number of 25 species in flax fields. These observations are important for the better management of weeds in the agroecosystems of Kashmir Himalaya.